Multifunctional hydrogels loaded with tellurium nanozyme for spinal cord injury repair - Jian Meng; Jingjing Sun; Jiali Kang; Shilei Ren; Miaomiao Xu; Runzhi Li; Xuhui Zhao; Yitong Yuan; Lei Xin; Ruiping Zhang (Materials Today Bio)
Spinal cord injury (SCI) results in severe neurological deficits due to disrupted neural pathways. While the spinal cord possesses limited self-repair capabilities, recent advancements in hydrogel-based therapies have shown promise. Polyphenol-based hydrogels, known for their neuroprotective properties, offer a suitable microenvironment for neural regeneration. In this study, a novel poly(lipoic acid)/poly(dopamine) adhesive hydrogel was developed as a versatile platform for delivering therapeutic agents. This hydrogel was loaded with methylcobalamin, a neurotrophic factor, and tellurium nanoenzymes, potent antioxidants. The nanoenzymes effectively mitigated oxidative stress and inflammation, while methylcobalamin promoted nerve regeneration. The combined therapeutic effects of the nanoenzymatic hydrogel demonstrated significant efficacy in repairing spinal cord injuries, highlighting its potential as a promising strategy for treating this debilitating condition.